Exploring the role of telehealth in providing equitable healthcare to the vulnerable patient population during COVID-19 - Shah, Dania A; Sall, Dana; Peng, Wesley; Sharer, Rustan; Essary, Alison C; Radhakrishnan, Priya (Journal of telemedicine and telecare, 2024)
The COVID 19 pandemic resulted in widespread telehealth implementation. Existent health disparities were widened, with under-represented minorities (URM) disproportionately affected by COVID. In this study, we assess the role of telehealth in improving access to care in the URMs and vulnerable populations. We noted a statistically significant increase in the number of visits in Hispanic or Latino patients (15.2% increase, < 0.01) and Black patients (19% increase, < 0.01). Based on payer type, there was a statistically significant increase in the number of visits in the Medicare (10.2%, p = 0.0001) and Medicaid (16.2%, < 0.01) groups. We also noted increased access to care with telehealth in patients who were 65 and older (10.6%, p = 0.004). This highlights the importance of telehealth in increasing access to care and promoting health equity in the URM and vulnerable patient populations.